Two Novel Dinuclear Cobalt Polypyridyl Complexes in Electro‐ and Photocatalysis for Hydrogen Production: Cooperativity Increases Performance. Issue 17 (21st July 2022) - Weder, Nicola; Grundmann, Nora S.; Probst, Benjamin; Blacque, Olivier; Ketkaew, Rangsiman; Creazzo, Fabrizio; Luber, Sandra; Alberto, Roger
Abstract: Syntheses and mechanisms of two dinuclear Co‐polypyridyl catalysts for the H2 evolution reaction (HER) were reported and compared to their mononuclear analogue (R1 ). In both catalysts, two di‐(2, 2'‐bipyridin‐6‐yl)‐methanone units were linked by either 2, 2'‐bipyridin‐6, 6'‐yl or pyrazin‐2, 5‐yl. Complexation with Co II gave dinuclear compounds bridged by pyrazine (C2 ) or bipyridine (C1 ). Photocatalytic HER gave turnover numbers (TONs) of up to 20000 (C2 ) and 7000 (C1 ) in water. Electrochemically, C1 was similar to the R1, whereas C2 showed electronic coupling between the two Co centers. The E (Co II/I ) split by 360 mV into two separate waves. Proton reduction in DMF was investigated for R1 with [HNEt3 ](BF4 ) by simulation, foot of the wave analysis, and linear sweep voltammetry (LSV) with in‐line detection of H2 . All methods agreed well with an (E)ECEC mechanism and the first protonation being rate limiting (≈10 4 m −1 s −1 ). The second reduction was more anodic than the first one. p K a values of around 10 and 7.5 were found for the two protonations. LSV analysis with H2 detection for all catalysts and acids with different p K a values [HBF4, p K a (DMF)≈3.4], intermediate [HNEt3 ](BF4 ), p K a (DMF)≈9.2 to weak [AcOH, p K a (DMF)≈13.5] confirmed electrochemical H2 production, distinctly dependent on the p K a values. Only HBF4 protonated Co I intermediates. The two metals in the dualcore C2 cooperated with an increase in rate to a competitive 10 5 m −1 s −1 with [HNEt3 ](BF4 ). The overpotential decreased compared to R1 by 100 mV. Chronoamperometry established high stabilities for all catalysts with TONlim of 100 for R1 and 320 for C1 and C2 . Abstract : Take two : Electrochemical investigations of different dinuclear cobalt‐polypyridyl water reduction catalysts reveal the effect of electrochemical coupling of both metal cores on the reduction mechanism.